Development and determination of the stability of cosmetic formulation with incorporation of natural products - Bouranen, Amira (2018)
Nowadays, natural products are gaining increased popularity as cosmetic ingredients due to their active properties and the different roles they can play in a single cosmetic formula, acting as active ingredients (moisturizers), fragrance (perfumes), excipients (surfactants) and additives (preservatives). The aim of this study is to formulate and subsequently evaluate the stability of an anti-aging gel based on natural product namely, bee pollen, which is used as pigment and active compound due to its intresting properties and essential oil from two varieties of thymus, Portuguese species Thymus zygis zygis and Tunisian species Thymus capitatus applied as natural preservative. The formulations selected were submitted to accelerated stability studies using various physical-chemical parameters such as pH, density, viscosity, themic analysis (freeze and thaw cycles),thermic stress, organoleptic characteristics (odor, color and aspect), UV spectrophotometric analysis, centrifuge test, tests of vibration, texture, spreading resistance and also through light test. The formulation was also evaluated for its resistance and activity against skin microorganisms such as: Staphylococcus aureus, Pseudomonas sp., Escherichia coli. The acute toxicity of the compound incorporated in the base formulation is determined through the evaluation of Brine shrimp (Artemia salina) mobility. The microbiological stability of the formulations is also evaluated through agar diffusion assays using cultures of Escherichia coli, Staphylococcus aureus, Pseudomonas ssp, Bacillus subtilis and Candida albicans. Regarding to the tests were done; centrifuge test and vibration test, there is no evidence of phase separation, which means that the formulation maintains its stability. For pH test, the formulations showed a suitable pH for body skin and no evidence of phase separation. The others tests are being evaluated.